Open VMS Alpha internals and data structures memory management - Goldenberg, Ruth E. (Amsterdam ; Boston : Digital Press, 2003)
OpenVMS Alpha Internals and Data Structures: Memory Management is an update to selected parts of the book OpenVMS AXP Internals and Data Structures Version 1.5 (Digital Press, 1994). This book covers the extensions to the memory management subsystem of OpenVMS Alpha to allow the operating system and applications to access 64 bits of address space. It emphasizes system data structures and their manipulation by paging and swapping routines and related system services. It also describes management of dynamic memory, such as nonpaged pool, and support for nonuniform memory access (NUMA) platforms. This book is intended for systems programmers, technical consultants, application designers, and other computer progressions interested in learning the details of the OpenVMS executive. Teachers and students of graduate and advanced undergraduate courses in operating systems will find this book a valuable study in how theory and practice are resolved in a complex commercial operating system. THE definitive reference describing how the OpenVMS kernel works Written by a top authority on OpenVMS systems Covers the latest version of OpenVMS.
Fundamentals and overview -- Memory management data structures -- Memory management system services -- Paging dynamics -- Working set list dynamics -- The swapper -- Pool management.
Includes bibliographical references and index.
Keywords: Operating systems (Computers).; OpenVMS; Memory management (Computer science); OpenVMS; Electronic books